2004
DOI: 10.1892/0891-6640(2004)18<625:praapc>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Renin Activity and Plasma Concentrations of Aldosterone, Cortisol, Adrenocorticotropic Hormone, and α-Melanocyte–Stimulating Hormone in Healthy Cats

Abstract: A pathogenetic role of the renin-angiotensin-aldosterone system has been implicated in cats in both systemic arterial hypertension and hypokalemic myopathy. Yet, measurement of plasma aldosterone concentrations (PACs) and plasma renin activity (PRA) has not unequivocally pointed to hyperaldosteronism as a cause of these conditions. To obtain appropriate reference ranges, this study included a large number (130) of healthy house cats of different breeds without a history of recent illness and plasma concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 38 publications
0
31
0
Order By: Relevance
“…Decrease in PRA may be the result of a combination of decreased renal mass, appropriate response to increased blood pressure or could be the consequence of age. Previous studies in cats have documented that PRA decreases with age, and cats in the nonazotemic normotensive group were significantly younger than those in other groups 16. Concern is often raised regarding the diagnosis of hypertension in cats without evidence of azotemia and the potential for white‐coat hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Decrease in PRA may be the result of a combination of decreased renal mass, appropriate response to increased blood pressure or could be the consequence of age. Previous studies in cats have documented that PRA decreases with age, and cats in the nonazotemic normotensive group were significantly younger than those in other groups 16. Concern is often raised regarding the diagnosis of hypertension in cats without evidence of azotemia and the potential for white‐coat hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…2,5 Although hypertension is associated with CKD in the cat, 1,3,4 the exact pathophysiologic mechanism(s) and interrelationship between the 2 conditions is still poorly understood. 6,7 Stimulation of the renin-angiotensin-aldosterone system (RAAS) occurs in human patients with CKD, [8][9][10] and this has been correlated with the severity of hypertension. 10 RAAS activation, through the effects of angiotensin-II and aldosterone, causes volume expansion, vasoconstriction, and a resultant increase in blood pressure.…”
mentioning
confidence: 99%
“…In cats, the gold standard to differentiate the primary hyperaldosteronism from the secondary hyperaldosteronism is the aldosterone: renin ratio, being 0.3 to 3.8 the established reference value (JAVADI et al, 2004;JAVADI et al, 2005). Thus, cats with adrenocortical tumors have very high plasma aldosterone activity and, in general, completely suppressed plasma renin activity, since the secretion is independent of the stimulation of the renin-angiotensin-aldosterone system (JAVADI et al, 2005).…”
Section: Diagnosis Aldosterone: Plasma Renin Ratiomentioning
confidence: 99%
“…Moreover, few laboratories offer the plasma renin test, which often requires the clinician to use the assessment of aldosterone activity as a single test (DECLUE et al, 2005). JAVADI et al (2004) determined a reference value of 80-450pmol L -1 (28.8 to162.2pg ml -1 ) for plasma aldosterone activity from studies in healthy cats, and reported that neither stress nor body condition affected the concentrations. Nevertheless, the same authors recommend that plasma aldosterone activity should always be based on serum potassium concentrations, as hypokalemia is decisive for reduced aldosterone secretion.…”
Section: Diagnosis Aldosterone: Plasma Renin Ratiomentioning
confidence: 99%
See 1 more Smart Citation